Organised Irresponsibility in the Post-Truth Era: Beck’s Legacy in Today’s World at Risk - Galantino, Maria Grazia (Italian Sociological Review, 2022)
The notion of ‘organized irresponsibility’, developed by Ulrich Beck in the eighties in relation to environmental risks, highlights the pervasiveness of decision-making processes in which it is no longer possible to identify an agent to whom cause and guilt can be attributed for the negative consequences of an action. This article claims that this concept remains analytically relevant for interpreting the transformations of responsibility in today’s process of oscillation between de-politicization and hyper-politicization. On one side, de-politicization represents decisions about the definition and management of global risks as technical, apolitical or even value-free, removing them – along with their corollary of responsibility – from the political arena. On the opposite side, the rhetoric and practices of hyper-politicization, based on the delegitimization of expert knowledge, reconfigure the decision-making space, revitalizing the role of the politician as a protagonist and opening the way to post-factual politics. The article argues, however, that coexistence of forms of post-factual politics and pressures towards the de-politicization of contentious issues produces what is only apparently a paradox.[...]